2006
DOI: 10.1093/annonc/mdl357
|View full text |Cite
|
Sign up to set email alerts
|

The anti-idiotypic antibody abagovomab in patients with recurrent ovarian cancer. A phase I trial of the AGO-OVAR

Abstract: Abagovomab s.c. vaccination is safe and well tolerated. The long vaccination schedule tended to be more effective with regard to AB3-induction and cellular cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 24 publications
2
46
0
1
Order By: Relevance
“…Interestingly, a correlation between specific humoral response to abagovomab and patients' survival has also emerged, so that randomized, controlled studies are now warranted to possibly prove clinical benefit (Reinartz et al, 2004). However, it seems fair to underline that other subsequent clinical trials on recurrent ovarian cancer (Pfisterer et al, 2006) and on a miscellanea of gynecologic/peritoneal primary tumors (Sabbatini et al, 2006) seem to confirm the encouraging results above. Moreover, pre-clinical data suggest that the integration of IL-6 within the abagovomab formulation -as a fusion protein -might improve efficacy by eliciting even more robust, CA125-specific humoral responses (Reinartz et al, 2003).…”
Section: Ovarian Cancermentioning
confidence: 98%
“…Interestingly, a correlation between specific humoral response to abagovomab and patients' survival has also emerged, so that randomized, controlled studies are now warranted to possibly prove clinical benefit (Reinartz et al, 2004). However, it seems fair to underline that other subsequent clinical trials on recurrent ovarian cancer (Pfisterer et al, 2006) and on a miscellanea of gynecologic/peritoneal primary tumors (Sabbatini et al, 2006) seem to confirm the encouraging results above. Moreover, pre-clinical data suggest that the integration of IL-6 within the abagovomab formulation -as a fusion protein -might improve efficacy by eliciting even more robust, CA125-specific humoral responses (Reinartz et al, 2003).…”
Section: Ovarian Cancermentioning
confidence: 98%
“…Recently, Pfisterer et al (62) performed a phase I trial in 36 recurrent ovarian cancer patients on the effect of subcutaneous administration of ACA 125 which was prematurely terminated due to patient withdrawal or disease progression. However, sc administration of ACA 125 did seem safe and was well-tolerated also in highly frequent dosage schedules (62).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…(27,58), one study administered through ip, iv and intradermal routes (58) and one study only used sc route of Mabs administration (62). The median number of patients included was 29 (range 3-447).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Two other phase I trials also demonstrated robust anti-anti-idiotypic antibody responses to abagovomab but were unable to demonstrate similar clinical responses due to differences in study design. 53,55 Given its overexpression in 90% of ovarian cancers, MUC1 is another promising target for monoclonal antibody therapy. 56 In a phase I trial of 26 women with persistent or recurrent ovarian cancer following platinum therapy, HMFG1, a murine anti-MUC1 antibody, resulted in a small but statistically significant rise in anti-HMFG1 and anti-MUC1 antibody responses in 38% of those completing the vaccination regimen.…”
Section: Cancer Immunotherapymentioning
confidence: 99%
“…51 Abagovomab (ACA125) is an anti-idiotypic antibody targeting CA125 which has also been examined in ovarian cancer patients. 53,54 Anti-idiotypic antibodies target primary anti-CA125 antibodies and boost the host immune response by mimicking the antigen of interest, producing anti-anti-idiotypic antibodies which also recognize this antigen. 15 In a phase Ib/II trial, abagovomab generated anti-anti-idiotypic antibodies and anti-CA125 antibodies in 68% and 50%, respectively, of 119 patients with advanced ovarian cancer.…”
Section: Cancer Immunotherapymentioning
confidence: 99%